Utility Model for Climate Change Adaptation at El Bosque University: Circular Economy Approach to Paper and Cardboard Waste - Jaime Alberto Romero-Infante; Juan Sebastian Leal-Cardenas; Javier Forero-Calderon (Universitas Diponegoro, 2024)
The impact of climate change has intensified the urgency of adopting sustainable practices in academic institutions, highlighting the need for innovative models that not only mitigate environmental impact, but also promote effective adaptation. This paper presents a pioneering approach focused on the development of a utility model designed specifically for climate change adaptation in the context of Universidad El Bosque. The paper focuses on the implementation of circular economy strategies, focusing on the efficient management of usable waste generated at the institution, specifically for cardboard and paper. This model, the result of interdisciplinary research, not only proposes tangible solutions to reduce the university's carbon footprint, but also establishes an exemplary paradigm for other educational institutions on their path towards environmental sustainability. In the development of the research and analysis of the data recorded by the Environmental Management Unit, it is determined that the rate of generation of usable waste from the university corresponds to a total of 19,475 kilograms for the 2023 period. Therefore, through the detailed analysis of the implementation and results obtained, this article seeks to contribute to the advancement of knowledge in a useful model for adaptation to climate change, with a practical and replicable approach in university environments and beyond, which consists of proposing a model for the implementation of a process of transformation of cardboard and paper waste, for the production of stationery items that can be sold in the university store, promoting reuse, circular economy and sustainability.